Fundamentals of Business - Skripak, Stephen J.; Parsons, Richard; Cortes, Anastasia; Open Textbook Library (Open Textbook Library, 2018)
An introductory textbook in business that covers a variety of topics: The Foundations of Business, Economics and Business, Ethics and Social Responsibility, Business in a Global Environment, Forms of Business Ownership, Entrepreneurship: Starting a Business, Management and Leadership, Structuring Organizations, Operations Management, Motivating Employees, Managing Human Resources, Union/Management Issues, Marketing: Providing Value, Accounting and Financial Information, and Personal Finances.
Preface: Teamwork in Business -- Chapter One: Foundations of Business -- Chapter Two: Economics and Business -- Chapter Three: Ethics and Social Responsibility -- Chapter Four: Business in a Global Environment -- Chapter Five: Forms of Business Ownership -- Chapter Six: Entrepreneurship:Starting a Business -- Chapter Seven: Management and Leadership -- Chapter Eight: Structuring Organizations -- Chapter Nine: Operations Management -- Chapter Ten: Motivating Employees -- Chapter Eleven: Managing Human Resources -- Chapter Twelve: Union Management Issues -- Chapter Thirteen: Marketing, Providing Value -- Chapter Fourteen: Accounting and Financial Information -- Chapter Fifteen: Personal Finances
In English.
Description based on print resource
Keywords: Management -- Textbooks; Business -- Textbooks